Literature Review: The Role of Green Leadership, Employee Engagement and ESG Implementation in Building Employee Affective Commitment - Murdiono, Jatmiko; Hamidah, Hamidah; Sariwulan, Rd. Tuty (International Journal of Advanced Multidisciplinary, 2025)
The purpose of this literature research is expected to help hypotheses for future authors in determining research related to employee affective commitment. Research articles on the role of green leadership, employee engagement and ESG implementation in building employee affective commitment are scientific literature articles in the scope of human resource management. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or conduct literature reviews of relevant previous articles. The data used in this study are secondary data, which are sourced from academic online media such as Thomson Reuters Journals, Sage, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Springer, Web of Science, Sinta Journals, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Green Leadership influences in Building Employee Affective Commitment; 2) Employee Involvement has an effect in Building Employee Affective Commitment; and 3) Implementation of Environmental Social and Good Governance has an effect in Building Employee Affective Commitment.